Does urban agriculture help prevent malnutrition? evidence from Kampala - Maxwell, Daniel G.; Levin, Carol E.; Dsete, Joanne (International Food Policy Research Institute, 1998)
Previous research has suggested that urban agriculture has a positive impact on the household food security and nutritional status of low-socioeconomic status groups in cities in Sub-Saharan Africa, but a formal test of the link between semisubsistence urban food production and nutritional status has not accompanied these claims. This paper seeks to redress this gap in the growing literature on urban agriculture through an analysis of the determinants of the nutritional status of children under five in Kampala, Uganda, where roughly one-third of all households in the sample engage in some form of urban agriculture. When controlling for other individual child, maternal, and household characteristics, these data indicate that urban agriculture has a positive, significant association with higher nutritional status of children, particularly height-for-age. Several pathways by which this relationship is manifested are suggested, and the implications of these results for urban food and nutrition policy and urban management are briefly discussed.